Politik Identitas dan Konsolidasi Demokrasi di Indonesia Pasca-Reformasi - Erinaldi Erinaldi (Universitas Mbojo Bima, 2024)
Post-Reformasi identity politics has become a significant phenomenon in Indonesian politics, with the potential to either strengthen or weaken democratic consolidation. This study aims to analyze the relationship between identity politics and democratic consolidation in Indonesia, focusing on the positive and negative impacts of identity politics on social and political stability. Using a qualitative approach and descriptive analysis, the research explores how identity politics has emerged in various political contexts in Indonesia and how it affects social cohesion and the integrity of democratic institutions. The findings show that while identity politics can enhance the representation of marginalized groups and enrich political participation, it also has the potential to trigger social polarization that may threaten the stability of democracy. Therefore, prudent management of identity politics by the government, political parties, and civil society is essential to maintain the balance between pluralism and national unity.